Influence of Amine‐Based Cationic Gemini Surfactants on Catalytic Activity of α‐Chymotrypsin. Issue 12 (7th September 2016) - Verma, Santosh Kumar; Ghritlahre, Bhupendra Kumar; Ghosh, Kallol K; Verma, Rameshwari; Verma, Shekhar; Zhao, Xiujian
ABSTRACT: The α‐chymotrypsin activity was tested in aqueous media with the presence of novel cationic amine–based gemini surfactant, with different spacer chain lengths and head group size, and also compared with the cationic cetyltrimethylammonium bromide (CTAB) and cetyltriphenylphosphonium bromide (CTPB) surfactants and aqueous buffer only. The p ‐nitrophenyl acetate (PNPA) hydrolysis rate was monitored in the presence of the surfactant concentration at 30°C. Most of these gemini surfactants gave higher catalytic activity as compared to cationic CTAB and CTPB. The highest superactivity was measured in the presence of gemini 16‐12‐16, [dodecanediyl‐1, 12‐bis(cetyldimethylammonium bromide)] surfactant at pH 7.5. The catalytic reaction follows the Michaelis–Menten mechanism. The catalytic rate constants, k cat, show the same profile that the catalytic affinity; K M being enhanced with increasing space chain length. The results are favorable for considering that the amine‐based gemini surfactant influences more than both the aqueous and cationic micellar media.